2017
DOI: 10.5301/ijbm.5000270
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 rs4072037 Polymorphism is Associated with Decreased Risk of Gastric Cancer: A Meta-analysis

Abstract: In conclusion, this meta-analysis suggested that rs4245739 polymorphism in the MUC1 gene may play a pivotal role in the pathogenesis of GC, especially for white populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It might be due to the small sample size of the study cohort but a study with larger sample size that compared the clinical factors between GC patients with or without family history of GC suggested that the effect of H. pylori infection on GC development decreases among GC patients with family history of GC [7]. Two recent meta-analysis studies have shown that the G allele of MUC1 rs4072037 is associated with a decreased risk of GC [38,39]. MUC1 rs4072037 affects the gene promoter, leading to reduced transcriptional activity and MUC1 [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to the small sample size of the study cohort but a study with larger sample size that compared the clinical factors between GC patients with or without family history of GC suggested that the effect of H. pylori infection on GC development decreases among GC patients with family history of GC [7]. Two recent meta-analysis studies have shown that the G allele of MUC1 rs4072037 is associated with a decreased risk of GC [38,39]. MUC1 rs4072037 affects the gene promoter, leading to reduced transcriptional activity and MUC1 [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 (Tab. 1) (References in Table 1: Chang et al, 2014[ 1 ]; Chen et al, 2015[ 2 ]; Cheng et al, 2015[ 3 ]; Dai et al, 2015[ 4 ]; Deng et al, 2014[ 5 ]; Gong et al, 2016[ 9 ]; Han et al, 2012[ 11 ]; He et al, 2013[ 12 ]; Hua et al, 2014[ 14 ]; Jia et al, 2017[ 16 ]; Kuang et al, 2014[ 17 ]; Li et al, 2015[ 20 ]; Li et al, 2016[ 18 ]; Li et al, 2017[ 19 ]; Liang et al, 2018[ 21 ]; Liu et al, 2011[ 23 ]; Liu et al, 2011[ 24 ]; Liu et al, 2014[ 25 ]; Liu et al, 2014[ 26 ]; Lu et al, 2012[ 27 ]; Ma et al, 2013[ 29 ]; Ma et al, 2013[ 30 ]; Ma et al, 2017[ 28 ]; Mo et al, 2016[ 31 ]; Mocellin et al, 2015[ 32 ]; Namazi et al, 2018[ 35 ]; Pabalan et al, 2015[ 36 ]; Peng and Xu, 2015[ 37 ]; Qi et al, 2016[ 38 ]; Qin et al, 2017[ 39 ]; Ribeiro et al, 2017[ 41 ]; Shen et al, 2014[ 47 ]; Shi et al, 2014[ 48 ]; Shi et al, 2017[ 49 ]; Shi et al, 2018[ 50 ]; Tian et al, 2012[ 52 ]; Wang et al, 2013[ 53 ]; Wang et al, 2014[ 54 ]; Wang et al, 2015[ 56 ]; Wang et al, 2015[ 57 ]; Wang et al, 2016[ 55 ]; Wu et al, 2015[ 58 ]; Xie et al, 2017[ 59 ]; Xu et al, 2014[ 61 ]; Xu et al, 2014[ 63 ]; Xu et al, 2015[ 62 ]; Xu et al, 2018[ 60 ]; Yadav et al, 2018[ 64 ]; Yan et al, 2013[ 65 ]; Yang et al, 2014[ 66 ]; Yang et al, 2016[ 67 ]; Ye et al, 2017[ 68 ]; Yu et al, 2014[ 69 ]; Zhang et al, 2012[ 72 ]; Zhang et al, 2013[ 71 ]; Zhang et al, 2015[ 74 ]; Zhang et al,...…”
mentioning
confidence: 99%